Oncologic and Functional Outcomes After Primary and Salvage Laryngopharyngoesophagectomy With Gastric Pull-Up Reconstruction for Locally Advanced Hypopharyngeal Squamous Cell Carcinoma - Meulemans, Jeroen; Couvreur, Floor; Beckers, Eline; Nafteux, Philippe; Van Veer, Hans; Vander Poorten, Vincent; Delaere, Pierre; Coosemans, Willy (Frontiers in Oncology, 2019)
Background/Purpose: Hypopharyngeal squamous cell carcinomas (SCC) are generally diagnosed in an advanced disease stage. A total laryngopharyngoesophagectomy with gastric pull-up reconstruction is a time tested surgical treatment in our centre for resectable failures or recurrences after primary treatment with organ preservation protocols (radiotherapy or chemoradiation), or as a primary surgical treatment for very advanced hypopharyngeal tumours. We present the results of our approach in terms of success rate, postoperative complications and functional and oncologic outcomes. Methods: We retrospectively reviewed the charts of all patients with hypopharyngeal SCC, who underwent laryngopharyngoesophagectomy with gastric pull-up reconstruction during the period 1989-2015. Results: The cohort included 60 patients. Mean follow-up was 32 months. Stage III and stage IV disease was present in 35% and 60% of patients, respectively. Successful reconstruction by intended gastric transposition was possible in 98.3% of cases. The in-hospital mortality rate was 8.3%. Two-year and five-year actuarial overall survival were 39.5% and 21.1%, respectively. Two-year and five-year actuarial disease specific survival were 58.5% and 46.6%, respectively. Two-year and five-year actuarial locoregional recurrence free survival were both 49.5%. A significantly lower locoregional recurrence free survival was observed in patients with pN+ disease compared to pN0 (Log rank, p<0.05). Complete oral intake was achieved in 82.7% of patients. Speech rehabilitation by means of Provox® puncture or electrolarynx was achieved in 66% of patients. Discussion/Conclusion: Total laryngopharyngoesophagectomy with gastric pull-up reconstruction for advanced stage hypopharyngeal SCC combines relatively good oncologic and functional outcomes in an prognostically unfavorable patient group.